Respuesta :

Answer:

18x+63

Step-by-step explanation:

First you've to simplfy it, multiply the first bracket by 5 and the second by 4.

= (5)(2x)+(5)(7) + (4)(2x)+(4)(7)

= 10x+35+8x+28

Combine Like Terms:

= 10x+35+8x+28

= (10x+8x)+(35+28)

= 18x+63

Answer:

[tex]63 + 18x[/tex]

Step-by-step explanation:

[tex]5(2x + 7) + 4(2x + 7) \\ \\ (10x + 35) + (8x + 28) = 18x + 63[/tex]

* The above answer is written in reverse, which is the exact same result.

I am joyous to assist you anytime.

ACCESS MORE